Treatment Options and Outcomes for Squamous Cell Carcinoma of the Nail Unit: A Systematic Review. Issue 3 (March 2022) - Ning, Anne Y.; Levoska, Melissa A.; Zheng, David X.; Carroll, Bryan T.; Wong, Christina Y.
Abstract : BACKGROUND: Nail squamous cell carcinoma (nSCC) is the most common nail unit malignancy. However, no studies to date have evaluated treatment options for nSCC based on recurrence data while controlling for invasion. OBJECTIVE: To identify temporal trends in nSCC treatment modalities and compare treatment outcomes based on invasion. METHODS AND MATERIALS: The authors performed a systematic review of articles published on PubMed, MEDLINE, and Scopus from inception to April 2020 reporting treatment of nSCC. The primary outcome was disease recurrence. RESULTS: Reports of nSCC treatments have increased in the past decade. Mohs micrographic surgery (MMS) is the most common treatment reported overall. The lowest recurrence rates for in situ nSCC were seen with wide surgical excision (WSE) and MMS. For invasive disease, the recurrence rates were lowest with amputation, MMS, and WSE. CONCLUSION: Complete surgical excision of nSCC with either WSE or MMS is associated with lower recurrence rates than limited excision and nonsurgical therapies, regardless of degree of invasion. The prognostic significance of in situ versus invasive disease remains unclear. Confirmation of complete excision may improve outcomes. Digital amputation is indicated for nSCC with bone invasion. Prospective studies and randomized controlled trials are needed to directly compare surgical modalities for nSCC. Abstract : Supplemental Digital Content is Available in the Text.